Welcome to Woomera. (Kanopy Streaming, 2015)
In recent years, Woomera has been synonymous with what the Australian government called its "immigration reception and processing centre". Once heralded as a model of suburban living, this historic town was reviled as a "desert jail". But the detention centre has closed and the town is in danger of closing too. A purpose-built defence village that once boasted 6000 residents has dwindled to a couple of hundred. Those who remain face an uncertain future. Their dilemma is a far cry from the late 1940s when the vast rocket range was first created in the outback to accommodate Britain's defence plans or later, when the Americans based themselves here to track missile launches from nearby Nurrungar. Through the eyes of residents past and present, this documentary reveals life in Woomera from the inside and follows the community's struggle to keep the town alive. As a government town however, its future is not necessarily in the hands of the locals. Marketing of the range has now been contracted out to a multinational company, with potential to capitalise on escalating global interest in weapons development to fight the "war on terror". Spanning half a century from the cold war to the space age and beyond, this is a film about ordinary people in a small town caught up in big events. A Film Australia National Interest Program in association with Flying Carpet Films. Produced with the assistance of the Australian Broadcasting Corporation. Copyright - 2011 National Film and Sound Archive of Australia. Executive Producer: Anna Grieve Producer: Steve Thomas, Kim Anning Director: Steve Thomas Writer: Steve Thomas DOP/Cinematographer: Philip Bull, Peter Zakharov Narrator/Presenter: Simon Burke.